2010
DOI: 10.1073/pnas.1000493107
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of wind farms on surface air temperatures

Abstract: Utility-scale large wind farms are rapidly growing in size and numbers all over the world. Data from a meteorological field campaign show that such wind farms can significantly affect near-surface air temperatures. These effects result from enhanced vertical mixing due to turbulence generated by wind turbine rotors. The impacts of wind farms on local weather can be minimized by changing rotor design or by siting wind farms in regions with high natural turbulence. Using a 25-y-long climate dataset, we identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
76
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(95 citation statements)
references
References 21 publications
3
76
0
Order By: Relevance
“…The warming effect from wind farms at night was firstly revealed and was attributed to the turbulence generated by the rotors enhancing the vertical mixing [13]. In the stable atmosphere when a warm layer overlies a cool layer, enhanced vertical mixing mixes warm air down and cold air up, leading to a warming near the surface [12,13].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The warming effect from wind farms at night was firstly revealed and was attributed to the turbulence generated by the rotors enhancing the vertical mixing [13]. In the stable atmosphere when a warm layer overlies a cool layer, enhanced vertical mixing mixes warm air down and cold air up, leading to a warming near the surface [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the possible impacts of wind farms on surface temperature, to date only a few studies have used the observed data from operational wind farms, such as the measurements in California [13] and in the Midwestern US [17]. The warming effect from wind farms at night was firstly revealed and was attributed to the turbulence generated by the rotors enhancing the vertical mixing [13].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In large wind farms, the interaction of the flow and the wind turbines is further complicated by the interaction of the wake of one wind turbine with neighbouring turbines. Besides the changed velocity field around the turbines, there is also evidence that wind turbines affect planetary boundary layer (PBL) processes due to the changed turbulence (Baidya Roy et al, 2004;Calaf et al, 2010;Baidya Roy and Traiteur, 2010;Barrie and KirkDavidoff, 2010;Wang and Prinn, 2010;Lu and Porté-Agel, 2011;Hasager et al, 2013;Fitch et al, 2013a).…”
Section: Introductionmentioning
confidence: 99%